Structure-Properties-Processing Relationships in Metallic Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the current Special Issue of Metals, we present six contributions from academia and industry. Based on their latest research developments, and achievements in their applied research field, the contributors elucidate the effect of temperature during forming operations that were closely analyzed via texture evaluation, present the opportunities that derive from microstructure and process simulation, and show how trace elements may affect critical properties in the performance of metallic materials. Bridging the gap between academia and industry, they provide all the necessary theoretical background through basic and applied research to meet the requirements for industrial application of the new and steadily optimized materials and concepts.